Moral distress and nursing competence: The mediating role of moral sensitivity and ethical climate - Oh, Gyu Young (Nursing ethics, 2025)
BackgroundNurses in long-term care often experience moral distress. While moral distress has been reported to negatively impact nursing competence and patient outcomes, some studies suggest that it may contribute positively to nursing competence. Thus, knowledge regarding the impact of moral distress on nursing competence remains limited and inconsistent.Research aimThis study aimed to identify the mediating effects of moral sensitivity and ethical climate on the relationship between moral distress and nursing competence.Research designThis was a quantitative study with a cross-sectional descriptive correlational design.Participants and research contextA survey was conducted with 175 registered nurses working in long-term care hospitals in Korea. Data were collected in September and October 2023. The survey measured moral distress, moral sensitivity, ethical climate, and nursing competence using the Moral Distress Scale, the Moral Sensitivity Questionnaire, the Hospital Ethical Climate Survey, and an instrument for measuring nursing competence in long-term care hospitals, respectively. The collected data were analyzed using SPSS Statistics version 27.0 and the PROCESS macro program.Ethical considerationThis study was approved by the Institutional Review Board. Informed consent was obtained from participants prior to data collection.FindingsMoral distress did not have a significant direct effect on nursing competence; however, it had a positive impact on nursing competence through the mediation of moral sensitivity and ethical climate. Moral sensitivity and ethical climate demonstrated a dual mediating effect in the relationship between moral distress and nursing competence.ConclusionThe findings of this study provide insights into how moral distress can positively contribute to nursing competence. Ensuring that nurses have high moral sensitivity and that organizations foster a positive ethical climate may help moral distress enhance nursing competence.